Analisis Strategi Live Streaming, Diskon, dan Sales Promotion terhadap Impulse Buying pada Marketplace Shopee dalam Perspektif Islam - Hamidah Tussifah; Farah Diba Aya Rosady (Politeknik Kampar, 2026)
The development of e-commerce has encouraged the use of increasingly intensive digital marketing strategies, which have the potential to trigger impulse buying behavior, especially among Generation Z. This study aims to analyze the influence of live streaming, discounts, and sales promotions on impulse buying among female students at Darussalam Gontor University Campus C who use the Shopee marketplace from an Islamic perspective. This study uses a quantitative method with a survey approach (questionnaire). Data was obtained through a Likert scale questionnaire distributed to 340 respondents and analyzed using multiple linear regression with the help of SPSS. The results show that, partially, live streaming, discounts, and sales promotions have a positive and significant effect on impulse buying with a significance value of 0.000. Simultaneously, the three independent variables also have a positive and significant effect on impulse buying. The conclusion of this study shows that digital marketing strategies can increase impulsive buying, but from an Islamic perspective, they need to be controlled so as not to encourage excessive consumption and remain in line with the principles of balanced consumption and Islamic values.